Hexafluorosilicic Acid as a Novel Reagent for the Desilylation of Silylacetylenes: Application in Sequential Sonogashira Coupling and Click Reaction - Sinai, Ádám; Mészáros, Ádám; Balogh, Ádám; Zwillinger, Márton; Novák, Zoltán (Synthesis, 2017)
Hexafluorosilicic acid was utilized as a novel, cheap, readily available, and environmentally benign alternative reagent for the desilylation of 1-trimethylsilylacetylenes. The applicability of the aqueous solution of the hexafluorosilicic acid was demonstrated in the sequential coupling of aryl halides and ethynyltrimethylsilane to afford internal acetylenes, benzofurans, and triazoles in one-pot Sonogashira–Sonogashira and Sonogashira–CuAAC reactions.
Keywords: alkynes; azides; cycloaddition; click reaction; cross-coupling; fluoride; palladium; heterocycles